Mormon Midwife - Smart, Donna T. (Utah State University, University Libraries, 1997)
Patty Session's 1847 Mormon Trail diary has been widely quoted and excerpted, but her complete diaries chronicling the first decades of Mormon settlement at Salt Lake City have never before been published. They provide a detailed record of early Mormon community life from Illinois to Utah through the eyes of Mormondom's most famous midwife. They also recount her important role in women's social networks and her contributions to community health and Utah's economy, to pioneer education and horticulture. Patty Sessions assisted at the births of humdreds of early Mormons and first-generation Utahns, meticulously recording the events. Shed had an active role in the founding of the Relief Society and health organizations. She spoke in tongues and administered spiritually as well as medically to the ill. Her diaries are a rich resource for early Mormon and Utah history.